2013
DOI: 10.1128/ec.00246-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Guanine Nucleotide Exchange Factor Rom2 in Cell Wall Integrity Maintenance of Aspergillus fumigatus

Abstract: Aspergillus fumigatus is a mold and the causal agent of invasive aspergillosis, a systemic disease with high lethality. Recently, we identified and functionally characterized three stress sensors implicated in the cell wall integrity (CWI) signaling of this pathogen, namely, Wsc1, Wsc3, and MidA. Here, we functionally characterize Rom2, a guanine nucleotide exchange factor with essential function for the cell wall integrity of A. fumigatus. A conditional rom2 mutant has severe growth defects under repressive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 39 publications
9
38
0
1
Order By: Relevance
“…It is primarily localized at the hyphal apex in proximity to the Rho‐GTPase Rho1 (Beauvais et al ., ). A proposed regulatory interaction with Rho1 links the β‐1,3‐glucan synthase complex to the cell wall integrity pathway of A. fumigatus (Dichtl et al ., ; Samantaray et al ., ), which is in good agreement with the model proposed in baker's yeast (Levin, ). It was shown that insertion of point mutations in A. fumigatus fks1 may result in resistance of laboratory strains to echinocandin antifungals (Gardiner et al ., ; Rocha et al ., ), and similar observations were also made in Candida albicans (Park et al ., ; Balashov et al ., ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is primarily localized at the hyphal apex in proximity to the Rho‐GTPase Rho1 (Beauvais et al ., ). A proposed regulatory interaction with Rho1 links the β‐1,3‐glucan synthase complex to the cell wall integrity pathway of A. fumigatus (Dichtl et al ., ; Samantaray et al ., ), which is in good agreement with the model proposed in baker's yeast (Levin, ). It was shown that insertion of point mutations in A. fumigatus fks1 may result in resistance of laboratory strains to echinocandin antifungals (Gardiner et al ., ; Rocha et al ., ), and similar observations were also made in Candida albicans (Park et al ., ; Balashov et al ., ).…”
Section: Introductionsupporting
confidence: 90%
“…In this respect, an active increase in the number of newly formed septa could additionally help to overcome echinocandin stress. We have previously shown that the cell wall stress sensor Wsc1 and downstream effectors of the cell wall integrity pathway (e.g., Rom2) are important to resist echinocandin antifungals (Dichtl et al ., ; Samantaray et al ., ). We therefore tested the hypothesis of a compensatory increase of septum formation upon echinocandin stress and any potential implications of the cell wall stress sensor Wsc1.…”
Section: Resultsmentioning
confidence: 99%
“…Whether these proteins directly interact with methanol or if the effects are due to relayed methanol, response signals (signal transduction) have not yet been elucidated. The signal transduction pathway may involve kinases, because PpRom2 naturally interacts with Rho‐like GTPases that in turn interact with kinases in signal transduction pathways (Samantaray, Neubauer, Helmschrott, & Wagener, ). Indeed, the effects of kinases on the activity of the AOX1 promoter have been studied separately, in knock‐out studies (Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The MAP kinase (Pmk1) signaling also has been found to remain active in the mtl2 and wsc1 disruptants of the fi ssion yeast Schizosaccharomyces pombe (Cruz et al 2013 ). Note that the line between Rom2 and Rho1 has been characterized solely for A. fumigatus within the genus Aspergillus ; the two proteins were shown to interact with each other by co-immunoprecipitation (Samantaray et al 2013 ). WSC cell wall integrity and stress response component domain, CFW Calcofl uor white, GEF guanine nucleotide exchange factor, G protein guanine nucleotide-binding protein, MAPK mitogen-activated protein kinase.…”
Section: Cell Wall Integrity Signaling Pathwaymentioning
confidence: 99%